Rahasia Sukses Mendriling Bola Mencakup Tips Dan Trik Dari Para Ahli Sepak Bola - Matla'ul Anwar; Mochamad Rizal Febriansyah Santoso; Oktavia Anggelika Fernanda; Rania Maritza Az Zahrah; Denny Oktavina Radianto (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Physical skills alone are not enough to be a good soccer player; Need to have strong tactical and mental abilities. In this article, research and interviews conducted with football experts who have proven themselves in the world of football are presented. They reveal the key to success in dribbling the ball. Experts provide advice and tricks that have helped them reach the peak of their performance, from basic techniques to more complex strategies. Technical skill development, tactical intelligence, mental readiness, and training and match preparation techniques are some of the elements discussed in this presentation. Soccer players of all levels can improve their abilities and achieve success in the game by understanding and applying the principles taught by experts.